Polycystic Kidney Disease Translating Mechanisms into Therapy (Springer New York, 2018)
This comprehensive guide to polycystic kidney disease captures the growing knowledge of this common, potentially-fatal and hereditary disease. The first two sections of the book provide an overview of PKD gene structures, mutations and pathophysiologic mechanisms. This is followed by chapters focused on PKD's clinical features, including renal and extrarenal manifestations, and appropriate management of patients. The final section covers current clinical trials and emerging therapies in PKD. Authored by experts in the field, this book provides the clinician and researcher with critical information on basic and translational science and clinical approaches in one concise resource.